2013
DOI: 10.1016/j.cmet.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Analysis in Nonalcoholic Fatty Liver Disease Suggests Distinct Disease-Specific and Remodeling Signatures after Bariatric Surgery

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disorder in industrialized countries. Liver samples from morbidly obese patients (n = 45) with all stages of NAFLD and controls (n = 18) were analyzed by array-based DNA methylation and mRNA expression profiling. NAFLD-specific expression and methylation differences were seen for nine genes coding for key enzymes in intermediate metabolism (including PC, ACLY, and PLCG1) and insulin/insulin-like signaling (including IGF1, IGFBP2, and PRK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
470
6
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 451 publications
(507 citation statements)
references
References 27 publications
15
470
6
2
Order By: Relevance
“…that has shown NAFLD-specific differences at DNA methylation levels of IGF1, a gene coding key enzymes of in insulin/insulin-like signaling. 13 This hypothesis is also partially supported by our findings that 30 out of the 67 of the differentially methylated CpG sites demonstrated a correlation of methylation on this site both with fasting insulin (n D 51) and transcription of a nearby gene. For example, the correlations between these NASH-associated CpG sites with the mRNA expression of genes such as LDHB and SQSTM1.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…that has shown NAFLD-specific differences at DNA methylation levels of IGF1, a gene coding key enzymes of in insulin/insulin-like signaling. 13 This hypothesis is also partially supported by our findings that 30 out of the 67 of the differentially methylated CpG sites demonstrated a correlation of methylation on this site both with fasting insulin (n D 51) and transcription of a nearby gene. For example, the correlations between these NASH-associated CpG sites with the mRNA expression of genes such as LDHB and SQSTM1.…”
Section: Discussionsupporting
confidence: 75%
“…We were also not able to differentiate the liver cell type composition between hepatocytes and inflammatory cells, which has been also the case in previous GW studies. 13,14 Thus, some changes in individuals with NASH could be related to changes in cell type composition. Nevertheless, we observed similar strength in the relationship between top-ranking NASH-associated CpG sites with both liver fibrosis and lobular inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the discovery stage, all publicly available Illumina DNAm datasets with phenotypic information on chronological age, BMI, and sex were analyzed. In these analyses of liver (12), adipose tissue (13), muscle (14), and blood (15,16), a strong positive (and expected) correlation between chronological age and DNAm age was observed with correlation coefficients ranging from 0.78 to 0.90 ( Fig. 1 A-D).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical evidence has suggested that bariatric surgery was able to partially reverse epigenetic alterations in the liver associated with NAFLD. Notably, reversing differentially methylated sites in NAFLD correlates with improvement in liver histology 119 .…”
Section: [H2] Epigeneticsmentioning
confidence: 99%